PTH-067 Setting Up A Hepatology Econsult Service – Beneficial For Patients And Primary Care, But Perhaps A Hardship For Secondary Care?. (9th June 2014) - Moreea, S; Appleby, VJ; Smith, B; Southern, PB; Connolly, J
Abstract : Introduction: Due to the heavy burden of liver disease, new policies are required to improve information flow between primary care (PC) and secondary care (SC). Outpatient visits are costly to PC, time consuming for patients and not always appropriate. Developing interventions to increase care available in PC is desirable and likely cost effective. We developed a hepatology eConsult (eC) service, allowing PC clinicians to send a referral and share a patient's medical record electronically with SC using a PC database. Methods: Service set up: Discussions between PC and SC identified a need for the service, and thorough review of the current Hepatology service was undertaken, focussing on current and projected working practices, service demands as well as clinicians job plans. Once eC was agreed in principle, a price of £23 per eC and a timescale of 7 days for eC to be completed was agreed with the CCG. A risk assessment of the service was performed and a comprehensive set of guidelines devised for use in PC, ensuring that only appropriate and timely referrals are made. Prior to launching the service, IT systems were updated, and appropriate training delivered to clinicians. To ensure smooth running of eC, user guides and support documents were created and distributed. Making and processing a referral using eC: Once a referral has been made in PC, it appears on-line and a hepatology secretary logs the referral, opening the episode of care and informs the designated hepatologist that a referral has been received. The eC takes approximately 15 min of consultant time to complete but varies depending on case complexity. Once completed, the hepatologist informs the secretary and they log a 'completed episode of care' ensuring the trust is paid for the clinical encounter. Referrals are audited on a 6 monthly basis. Results: Between March 2012 – Oct 2013, 81 eC were completed (12 in months 1–6, 16 in months 7–12, 40 in months 13–18, 13 in months 19–20). A SC appointment was avoided in 78% of patients (n = 63) resulting in a cost saving to PC of £16, 443 [63 x eC(£23) = 1, 449 vs 63 x new patient referrals (£181) = £11, 403 + 1x follow up/patientn (£103) = £6489). Median response time for eC was 2 days, 43% were completed within the same working day. Conclusion: Hepatology eC is beneficial for patient care, with specialist advice being provided within one working day in a substantial number of cases, and is clearly cost effective, making eC popular with PC. However, until a more slim-line IT system is developed reducing the number of steps involved in completing an eC, and the cost per eC increased, it appears to be beneficial for all parties except SC. Disclosure of Interest: None Declared.